Project IICE : Inspiring Interdisciplinary Collaboration Experiences - Dow , Tracy; Gilbert , Adam; Sawyer , Megan; Weinstein , Michael; York , Katharine (Experiential Learning and Teaching in Higher Education, 2022)
Project IICE was a multi-disciplinary learning experience designed for students at Southern New Hampshire University. Students worked together in teams to communicate scientific data that was initially collected by an Introductory Botany class. Students in this course measured trees and recorded variables, including tree height, diameter, species, and canopy cover. They shared the data with students in freshman Statistics courses, who analyzed mathematically for trends. Finally, students in Graphic Design used the data to create visual representations and icons. Students collaborated in groups that were randomly assigned across all of the courses to include members of each discipline. During the process, each student was required to help others in the group understand the meaning of the data, through the collection, analysis, and design phases. In the final group poster presentations, students explained the meaning and value of each part. The emphasis was on their ability to communicate the significance of each part of the process, which helped them appreciate how the discipline they were working in contributed to the overall success of the project. The real-world data provided a context for students to experience working in cross-discipline teams, and sharpened communication skills.